The media, personal digital criminal legacies and the experience of offenders convicted of occupational fraud and corruption. Issue 1 (2nd October 2019) - Shepherd, David; Beatty, Emma; Button, Mark; Blackbourn, Dean
Abstract : Purpose: The purpose of this paper is to explore the impact of media coverage on offenders convicted of occupational fraud and corruption in the UK. It examines the extent of media coverage and provides insights into the experiences of offenders. Design/methodology/approach: The study is based upon interviews with 17 convicted offenders, and on a content analysis of one national and two regional newspapers in the UK. Findings: The findings suggest that offenders convicted of occupational crime and corruption are more likely to experience media coverage than previously assumed and that personal digital criminal legacies create long-term labels which lead to economic strains and social fractures that hinder productive reintegration into society. Research limitations/implications: The research is limited by a small sample frame in the UK. Nevertheless, the findings suggest further research is required as they have important implications for privacy and rehabilitation. Practical implications: In particular, offenders and their families need support in dealing with their personal digital criminal legacies, accessing their privacy rights and coping with the strains created by online stigmatisation. From a policy perspective, the existing regulatory framework that supports rehabilitation in the UK, especially the increasingly archaic Rehabilitation of Offenders Act 1974, requires close examination and debate to ensure it is fit for the digital era. The findings also suggest that policies, practices and responsibilities of the public sector in employing offenders need to be examined. Originality/value: It is a rare study of white-collar offenders after their release from prison. The findings are of relevance to criminal justice policy makers, rehabilitation services and academics.